Making Distance Visible: Assembling Nearness in an Online Distance Learning Programme - Ross, Jen; Gallagher, Michael Sean; Macleod, Hamish (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Online distance learners are in a particularly complex relationship with the educational institutions they belong to (Bayne, Gallagher, & Lamb, 2012). For part-time distance students, arrivals and departures can be multiple and invisible as students take courses, take breaks, move into independent study phases of a programme, find work or family commitments overtaking their study time, experience personal upheaval or loss, and find alignments between their professional and academic work. These comings and goings indicate a fluid and temporary assemblage of engagement, not a permanent or stable state of either “presence” or “distance”. This paper draws from interview data from the “New Geographies of Learning” project, a research project exploring the notions of space and institution for the MSc in Digital Education at the University of Edinburgh, and from literature on distance learning and online community. The concept of nearness emerged from the data analyzing the comings and goings of students on a fully online programme. It proposes that “nearness” to a distance programme is a temporary assemblage of people, circumstances, and technologies. This state is difficult to establish and impossible to sustain in an uninterrupted way over the long period of time that many are engaged in part-time study. Interruptions and subsequent returns should therefore be seen as normal in the practice of studying as an online distance learner, and teachers and institutions should work to help students develop resilience in negotiating various states of nearness. Four strategies for increasing this resilience are proposed: recognising nearness as effortful; identifying affinities; valuing perspective shifts; and designing openings.